Peningkatan Kompetensi Guru TK dan PAUD dalam Pembuatan Bahan Ajar Interaktif - Fryonanda, Harfebi; Novi; Mardiah , Ainil; Widianti , Nina; Nissa, Wirda (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Training on making interactive teaching materials using Canva for kindergarten and early childhood education teachers in Lubuk Tarok District aims to improve teachers' technological skills and creativity in designing exciting teaching materials. This training was conducted in response to teachers' challenges in utilizing educational technology, especially in areas with limited access to technology. The training method included an introduction to Canva, introductory training sessions, workshops, guided practice, and independent practice, followed by participant evaluations. The results showed a significant increase in teacher competence, confidence, and motivation in using technology. The final evaluation showed high scores in reliability, responsiveness, and empathy. Teachers reported that the interactive teaching materials created were able to increase student engagement and positive responses during learning activities. The long-term impact of this training is expected to maintain the skills that have been acquired and become a model for development in other areas with appropriate adaptations. The analysis of the results also identified several challenges faced by participants during the training, providing insights for improving future training. This training has been proven to significantly contribute to improving the quality of early childhood education through integrating technology into teaching.